Film Hawk [videorecording (DVD)] - Hawk, Robert; Smith, Kevin, 1970-; Burns, Edward, 1968- (MVD Visual, 2023)
An intimate look at Bob Hawk, from his early years as a young gay child of a Methodist minister to the man who shepherded the careers of and selflessly championed filmmakers on some of the most influential independent films and filmmakers of our time, in this critically acclaimed feature documentary written and directed by JJ Garvine and Tai Parquet.